Globe amaranth as an alternative source of natural red-violet colorants: an optimization study addressing current needs of the industrialized world - Roriz, Custódio Lobo (2018)
Plant-derived colorants have an extensive history of use around the world for enhancing food and clothing. However, artificial colorants are nowadays massively used in the food industry due to their abundance, cheaper prices, and bright colors. These additives are recognized for their potentially toxic and allergic effects to humans, and contribution to environmental pollution. This leads the current, more conscientious consumer to opt for foods containing natural coloring agents, which may also have health-promoting effects. A current challenge is to find natural matrices rich in molecules with coloring capacity and optimize their recovery and stabilization. A chemical prospecting study allowed us to select globe amaranth (Gomphrena globosa L.) as a rich source of betalains, a group of chromoalkaloids that can be divided in betacyanins (red-violet pigments) and betaxanthins (yellow pigments). Given the powerful colorant capacity of these molecules and the great interest to use natural colorants in the food industry to replace the artificial counterparts, this study aimed to optimize the production of a natural colorant from globe amaranth using efficient and more sustainable processes. The non-conventional methods of microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE) were used for samples processing. For production of the coloring ingredients, a full factorial design was implemented combining the independent variables of processing time (t), temperature (T) or power (P), ethanol concentration (Et) and solid/liquid ratio (S/L) and response surface methodology was used for optimization. The extraction yield and coloring capacity of the extracts was maximized based on different responses: extracted residue, determined by gravimetric analysis; betacyanins levels, monitored by high-performance liquid chromatography coupled with mass spectrometry; and color intensity, measured by UV-Visible spectroscopy and colorimetry. The optimum processing conditions for MAE (t= 8 min, T= 60 ºC, Et= 0%, and S/L= 5 g/L) originated 39.6±1.8 mg/g, while for UAE (t= 22 min, P= 500%; Et= 0%, and S/L= 5 g/L) led to 46.9±4.8 mg/g, which supports the use of UAE for recovery of betacyanins from the studied plant. This study highlighted globe amaranth as an alternative source of red-violet colorants with high potential to be used as natural food additives.